2000
DOI: 10.1182/blood.v96.9.2987
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of dominant T-cell clones in peripheral blood in 363 patients presenting consecutively with a clinical suspicion of cutaneous lymphoma

Abstract: It is now widely accepted that polymerase chain reaction (PCR) analysis of cutaneous T-cell clonality is of diagnostic value in cutaneous T-cell lymphomas (CTCLs) and most helpful in the diagnosis of mycosis fungoides (MF). However, the diagnostic and prognostic value of circulating clonal T cells remains unclear. We studied T-cell clonality in the peripheral blood (PB) and the cutaneous lesion, sampled at the same time, in 363 consecutively seen patients with a clinical suspicion of cutaneous lymphoma. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(46 citation statements)
references
References 30 publications
5
35
1
4
Order By: Relevance
“…Interestingly, Delfau‐Larue and colleagues noted that 57% of patients in their study with monoclonal T‐cell proliferation in skin and blood were erythrodermic . The improvement seen in patient 2 after reducing the volume of T‐cell clones using ECP suggests that these clones could be driving the erythrodermic response.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, Delfau‐Larue and colleagues noted that 57% of patients in their study with monoclonal T‐cell proliferation in skin and blood were erythrodermic . The improvement seen in patient 2 after reducing the volume of T‐cell clones using ECP suggests that these clones could be driving the erythrodermic response.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of monoclonal T‐cell proliferation in the skin, blood and bone marrow in patients with suspected erythrodermic CTCL is unclear. Monoclonal T‐cell proliferation can occur as a reactive process in the skin of various benign dermatoses, with a prevalence of 14% among patients with contact dermatitis, drug‐induced dermatoses and pseudolymphoma . Delfau‐Larue and colleagues demonstrated that among 46 patients with suspected CTCL with monoclonal T‐cell proliferation in the skin and blood, 33 (72%) had skin histology suggestive of CTCL.…”
Section: Discussionmentioning
confidence: 99%
“…[1,5,29] However, there is considerable discussion regarding the signi cance of dominant T-cell clones as a hallmark of T-cell malignancy because small populations of clonally expanded T-LGLs are revealed in healthy individuals and in an exuberant reactive response. [30][31][32][33][34] Considering that the difference between RA-associated T-LGLL and FS often depends on a single test with well-known gray areas in interpretation and limitations, [35] it is necessary look for additional distinctions. We can use mutations in STAT3 and STAT5b genes as molecular markers for T-LGLL diagnostics, [36] but their prevalence in FS and their diagnostic value for differential diagnosis between FS and RA-associated T-LGLL are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The author concludes that the presence of an identical T‐cell clone in the skin coupled with detection of an identical clone in the blood (or lymph node) is a fairly specific diagnostic criterion for E‐CTCL as indicated by Dr Russell‐Jones and others, 55 but ‘false positives’ may still occur in about 5% of cases, and the diagnostic sensitivity varies according to the PCR‐method used [14/52 (27%) for PCRγ‐DGGE and 6/16 (38%) for PCRγ‐SSCP].…”
Section: Personal Experience With Molecular Analysis For Erythrodermimentioning
confidence: 89%
“…Somewhat unexpectedly, a dominant T‐cell clone was found in skin samples from 11/45 (24%) of our cases considered to have non‐malignant disease compared with 33/68 (49%) of E‐CTCL cases (p = 0.017). While most investigators have found a very low frequency of T‐cell clones using PCR‐based techniques in benign inflammatory disease, Delfau‐Larue reported finding a clone in skin samples from 17/72 (24%) benign cases with a GC‐clamp multiplex PCRγ‐DGGE technique compared with 17/22 (77%) specimens from patients with SS 55 . Thus, the detection of a T‐cell clone may depend on the PCR method used.…”
Section: Personal Experience With Molecular Analysis For Erythrodermimentioning
confidence: 99%